ASYMMETRIC DYNAMICS OF RENEWABLE ENERGY CONSUMPTION AND ECONOMIC GROWTH FOR SUSTAINABLE DEVELOPMENT IN PAKISTAN (Contemporary Journal of Social Science Review, 2025)
Growing economic growth, rising in energy demand, urbanization, and environmental deterioration are all contributing factors that create pressure to  achieve sustainable development. The sources of non-renewable energy usage contributed to increase carbon emission. The shifting to renewable energy consumption  is becoming an important policy goal. Hence, this study main aim is to examine the Asymmetric effects of renewable energy consumption, energy intensity, and urbanization on sustainable development in the context of Pakistan. This study used the annual time-series data covering the time-period from 1990-2024. To capture the Asymmetric effects of the candidate variables, this study used the Non-Linear Autoregressive Distributed Lag Approach (NARDL). The study findings conjecture that a positive shocks in renewable energy consumption, economic growth, and energy intensity significantly contributes to increase sustainability. However, a negative shock in renewable energy consumption leads to decrease the sustainability level. Increased energy intensity generally has an  adverse effect , but managed and planned urbanization promotes green growth. The study findings conjecture that Pakistan may increase  the adoption of renewable energy by offering financial incentives, improving energy efficiency through technical developments, encouraging sustainable urbanization, and incorporating environmental concerns into economic growth strategies, with these focused efforts, Pakistan will be in a position to achieve low-carbon, sustainable economy.